Binding Mode Investigation of Polyphenols from Scrophularia Targeting Human Aldose Reductase Using Molecular Docking and Molecular Dynamics Simulations - Abinaya Manivannan; Prabhakaran Soundararajan; Yoo Gyeong Park; Sugunadevi Sakkiah; Byoung Ryong Jeong (Journal of Chemistry)
Aldose reductase (ALR2), a vital enzyme involved in polyol pathway, has befitted as a novel drug target in antidiabetes drug discovery process. In the present study, the binding mode and pharmacokinetic properties of potential polyphenolic compounds with reported aldose reductase inhibitory activity from the genus Scrophularia have been investigated. The human ALR2 enzyme (PDB ID: 2FZD) acted as the receptor in the current study. Among the compounds investigated, acacetin, a methoxy flavonoid, displayed the stable binding to the active site of ALR2 with least binding energy value. Molecular interaction analysis revealed that acacetin interrupts the proton donation mechanism, necessary for the catalytic activity of ALR2, by forming H-bond with Tyr48 (proton donor). In addition, acacetin also possessed favorable ADME properties and complies with Lipinski’s rule of 5 representing the possible drug-like nature compared to other polyphenols. Interestingly, the biological activity predictions also ranked acacetin with higher probability score for aldose reductase inhibition activity. Moreover, the molecular dynamics simulation of ALR2-acacetin complex was validated for the stability of ligand binding and the refined complex was used for generation of receptor-ligand pharmacophore model. Thus, the molecular insights of receptor-ligand interactions gained from the present study can be utilized for the development of novel aldose reductase inhibitors from Scrophularia.